Literature Review Sistem Informasi Manajemen Rumah Sakit dalam Pengambilan Keputusan - Aulia Dini Ayuningtias (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Hospital Information Sistems (HIS) integrating Decision Support Sistem (DSS) modules have been proposed to enhance operational efficiency and clinical decision-making in hospital settings. This study conducted a systematic literature review of 80 empirical articles published between January 2020 and May 2025, following PRISMA guidelines, to examine how DSS integration within HIS supports managerial and clinical decisions. Findings indicate that DSS integration improves patient registration speed by an average of 25, reduces medication errors by up to 15, and facilitates resource allocation and performance monitoring via analytic dashboards. Organizational resistance and inadequate IT infrastructure remain significant barriers. These results underscore the importance of designing user-friendly dashboards, implementing transparent inference engines, and adopting comprehensive change management strategies. The study extends the Technology Acceptance Model with a perceived risk construct and offers practical recommendations for developers and hospital managers aiming to optimize HIS–DSS implementation.